Costs of occupational injuries in agriculture. - Leigh, J. P. (Association of Schools of Public Health, 2001)
OBJECTIVE: This study was conducted to estimate the costs of job-related injuries in agriculture in the United States for 1992. METHODS: The authors reviewed data from national surveys to assess the incidence of fatal and non-fatal farm injuries. Numerical adjustments were made for weaknesses in the most reliable data sets. For example, the Bureau of Labor Statistics (BLS) Annual Survey estimate of non-fatal injuries is adjusted upward by a factor of 4.7 to reflect the BLS undercount of farm injuries. To assess costs, the authors used the human capital method that allocates costs to direct categories such as medical expenses, as well as indirect categories such as lost earnings, lost home production, and lost fringe benefits. Cost data were drawn from the Health Care Financing Administration and the National Council on Compensation Insurance. RESULTS: Eight hundred forty-one (841) deaths and 512,539 non-fatal injuries are estimated for 1992. The non-fatal injuries include 281,896 that led to at least one full day of work loss. Agricultural occupational injuries cost an estimated $4.57 billion (range $3.14 billion to $13.99 billion) in 1992. On a per person basis, farming contributes roughly 30% more than the national average to occupational injury costs. Direct costs are estimated to be $1.66 billion and indirect costs, $2.93 billion. CONCLUSIONS: The costs of farm injuries are on a par with the costs of hepatitis C. This high cost is in sharp contrast to the limited public attention and economic resources devoted to prevention and amelioration of farm injuries. Agricultural occupational injuries are an underappreciated contributor to the overall national burden of health and medical costs.